Dextran sulfate inhibits the invasion, migration, and programmed death-ligand 1 expression in human gastric cancer cells by affecting the M2 tumor-associated macrophage polarization - Shang, Jing; Xu, Yuanyi; Tao, Yuejia; Li, Bing; Li, Mengqi; Guo, Jiaxin; Yan, Lvjun; Huang, Yunning; Ma, Qian (Frontiers in Oncology, 2025)
ObjectiveThe aim of this study was to investigate the role of dextran sulfate (DS) in M0-to-M2 macrophage polarization and its effect on programmed death-ligand 1 (PD-L1) expression, invasion, migration, proliferation, and apoptosis of human gastric cancer cells (HGCCs) through its action on M2 tumor-associated macrophages (M2-TAMs).MethodsThe effects of DS on M0-to-M2 macrophage polarization and HGCC behavior were examined. CD163 expression was analyzed to determine macrophage polarization, whereas HGCC proliferation, apoptosis, migration, and invasion and PD-L1 expression were quantified. The effect of DS on tumor development was evaluated in an in vivo nude mouse model of intraperitoneal implantation by assessing the size and number of implanted nodules. The study also analyzed the association between tumor CD163 and PD-L1 expression.ResultsDS inhibited M0-to-M2 macrophage polarization and HGCC proliferation, invasion, and migration while increasing apoptosis and decreasing PD-L1 expression. DS decreased the number and the size of metastatic tumor nodules in nude mice while decreasing CD163 expression. CD163 expression is positively associated with PD-L1 expression (p < 0.01, R2 = 0.1613, N = 46).ConclusionDS inhibits the macrophage transition to the M2 phenotype, leading to a reduced PD-L1 expression and HGCC proliferation, invasion, and migration while increasing cell death.